2008
DOI: 10.1155/2008/510584
|View full text |Cite
|
Sign up to set email alerts
|

On anisotropic Triebel‐Lizorkin type spaces, with applications to the study of pseudo‐differential operators

Abstract: A construction of Triebel-Lizorkin type spaces associated with flexible decompositions of the frequency spaceℝdis considered. The class of admissible frequency decompositions is generated by a one parameter group of (anisotropic) dilations onℝdand a suitable decomposition function. The decomposition function governs the structure of the decomposition of the frequency space, and for a very particular choice of decomposition function the spaces are reduced to classical (anisotropic) Triebel-Lizorkin spaces. An e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 33 publications
0
45
0
Order By: Relevance
“…Before stating our result, we recall the definitions and the molecular characterizations of these spaces. For an extensive treatment of these spaces, the reader is referred to [4,5,6]; see also [2].…”
Section: Anisotropic Homogeneous Triebel-lizorkin and Besov Spacesmentioning
confidence: 99%
“…Before stating our result, we recall the definitions and the molecular characterizations of these spaces. For an extensive treatment of these spaces, the reader is referred to [4,5,6]; see also [2].…”
Section: Anisotropic Homogeneous Triebel-lizorkin and Besov Spacesmentioning
confidence: 99%
“…To construct the resolution of the identity, we use a suitable covering of the frequency space. For a much more detailed discussion of the T-L type spaces see [2], and for the associated modulation spaces see [1].…”
Section: Triebel-lizorkin Type Spacesmentioning
confidence: 99%
“…It can be shown that F s p,q (h) depends only on h up to equivalence of the norms (see [2,Proposition 5.3]), so the T-L type spaces are well-defined and similar for the modulation spaces. Furthermore, they both constitute quasi-Banach spaces, and for p, q < ∞, S is dense in both (see [2,Proposition 5.2]).…”
Section: Definition 28mentioning
confidence: 99%
See 2 more Smart Citations